ANALISA PENDAPATAN USAHA JASA PENGOLAHAN GULA MERAHEBU DI KILANG TEBU ZAHRATUL AZHAR KAMPUNG BLANG MANCUNG BARAT KECAMATAN KETOL KABUPATEN ACEH TENGAH - Hikmah, Hikmah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2021)
Sugar cane is one of the agribusiness-oriented agricultural commodities and is a raw material in processing brown sugar cane (GTM). The purpose of this research is to determine the costs and revenues of GTM processing services at the Zahratul Azhar Sugar Cane refinery in Blang Macung Barat, Ketol District, Central Aceh District. The analysis used in this study is the analysis of income, R / C Ratio and Break Event Point (BEP). The results showed that sugarcane refineries incurred costs in the GTM processing services business of Rp.2,682,251 / month, with production yields of 720kg rental services and an average price of 5,200 / kg, so that the revenue obtained was Rp.3,744,000 and the income earned by the refinery is Rp. 1,061,749 / month. R / C Ratio> 1 which is 1.39 means that the refineries that produce GTM are worth continuing. BEP value of sugar cane refinery acceptance is Rp.757,641, if the revenue is below the value of BEP, the service business suffers a loss. BEP value of sugar cane refinery production is Rp. 515.8 kg while the production of rental wages is 720kg, the production of brown sugar cane is greater than the BEP Production so this business is worth continuing. BEP Value The price of sugar cane refinery is Rp. 3,725 / kg and the price of cane brown sugar Rp.5,200 / kg, meaning that the price of GTM is greater than the BEP Price so this business is worth the effort. Keywords: GTM Processing Services, Revenue.